Selecting soybean (Glycine max) genotypes for insertion height of the lowest pod, the useful trait for combine harvester - RAMTEKE, RAJKUMAR; SINGH, DEVVRAT; MURLIDHARAN, POOJA (The Indian Journal of Agricultural Sciences, 2012)
Field experiments were conducted during 2008 and 2009 using 90 genotypes to screen for height of insertion of the lowest pod, the trait useful for combine harvester. Data was recorded on plant height (cm), height of insertion of the lowest pod (cm) when erect, lodging of the plant in degrees (ø), stem diameter (cm), number of nodes, number of branches and yield. Results of analysis of variance showed significant differences among genotypes in terms of traits under study, which indicate the existence of genetic variation. Correlation coefficient indicated that the grain yield was not significantly associated with all studied traits, which showed non-significant association. Plant height and nodes were negatively correlated with lodging of plants in degrees. First pod height was significant and positively associated with height as well as number of nodes/plant. Stem diameter was positively associated with the nodes/plant. Highest yield was observed in genotypes JS 95-60, Co Soya 2, JS 71-05, MACS 450, VL Soya 21, MAUS 47, KB -79, MAUS 81, PS 1225, NRC 37 and MAUS 71 and was found at par with JS 95-60. However, the genotypes JS 71-05, MAUS 47, PS 1225, NRC 37 and MAUS 71 had a yield at par with JS 95-60, with the lodging angle in degrees (> 65.00°), having pod height above 12 cm, these genotypes are recommended for mechanical harvesting.